SISTEM PENDUKUNG KEPUTUSAN PENERIMA BANTUAN EKONOMI LEMAH MENGGUNAKAN METODE PROFILE MATCHING - Pinkan Steffany Pakasi (Sekolah Tinggi Manajemen Informatika dan Komputer (STIMIK) Bina Mulia Palu, 2023)
This study aims to design and implement a Decision Support System (DSS) to determine recipients of economic aid for the underprivileged in Palu City using the Profile Matching method. The main problem addressed is the subjective and manual selection process currently in use, which often leads to inaccuracies and social discontent. The proposedsolution is a computerized system that automates the matching process between potential recipient profiles and predetermined aid criteria. The research method employed was qualitative, involving observation, interviews, and literature study, with system development following the waterfall model. The results demonstrate that the developed system successfully improves the accuracy, transparency, and efficiency of the recipient selection process. Black box and white box testing confirmed the system's logical and functional correctness, while feedback from key informants indicated a high level of user satisfaction. The study's contribution lies in providing a practical tool for the Social Service Office and adding to the theoretical body of knowledge on the application of Profile Matching in DSS for social aid allocation. The system offers a significant benefit over the pre-existing manual method by reducing subjectivity, minimizing errors, and enabling data-driven, equitable decision-making.